Perilaku Anggota Kelompok Nelayan Wanasari dalam Menjaga Kelestarian Hutan Mangrove di Kelurahan Tuban, Kecamatan Kuta, Kabupaten Badung - I MADE DWI WIDNYANA; NI WAYAN SRI ASTITI; M.TH. HANDAYANI. (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract The Behavior of the Wanasari Fisherman’s Group Members in Preserving the Mangrove Forest in the Village of Tuban, Kuta Sub-District, Badung Regency Damage of mangrove forest caused by human habitual who not understand about the importance of mangroves existance,because the goverments do not give socialiszation and also they did not involve them self in planning, implementation and controling process. The purpose of this study is to determine the behavior of members of the Group of Fisherman of Wanasari seen from the aspects of knowledges, attitudes, and skills in preserving mangrove forests and the constraints faced by members of the Fisherman Group of Wanasari in preserving mangrove forests. Data analysis was conducted by using descriptive qualitative analysis method. Based on the research results, it was found that the behavior of members of the Wanasari Fisherman Group in preserving mangrove forests was categorized as good, with the score of 79.40%. This is supported by the high respondents knowledge, with the score of 82.30%, the attitude of the respondents belong to agree, with the score of 76.30% and the skills of respondents was classified as good, with the score of 79.60%. In process improving attitude in knowledges, attitude and skill aspecs, It suggested to Fisherman Group Members of Wanasari in order tohow to know mangroves cultivates such as breeding, planting, maintenance and utilization of mangroves that way it will be continue. Keywords: mangrove forests, behavior, member of fisherman group.